Perlindungan Hukum dan Pertimbangan Hakim dalam Menentukan Hak Asuh Anak Pasca Perceraian - Aprilia Hasanah , Cantika (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This article examines the legal protections and the considerations made by judges in determining child custody following divorce, based on the principles of justice, utility, and legal certainty. In divorce cases, child custody issues frequently emerge as one of the primary conflicts that must be resolved by the court. Judges play a critical role in ensuring that decisions are made after careful consideration of various factors, including legal, psychological, and sociological aspects, to safeguard the best interests of the child. The principle of the "best interest of the child" serves as the fundamental guideline in judicial rulings, prioritizing the physical, emotional, and psychological well-being of the child. Furthermore, legal frameworks such as Law No. 1 of 1974 on Marriage, Law No. 23 of 2002 on Child Protection, and the Compilation of Islamic Law provide essential foundations for judges’ decision-making processes regarding child custody.